2022
DOI: 10.1177/07067437211070648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Mental Health Interventions Among Children, Adolescents, and Adults Not Quarantined or Undergoing Treatment Due to COVID-19 Infection: A Systematic Review of Randomised Controlled Trials

Abstract: Objectives Our objective was to assess the effects of mental health interventions for children, adolescents, and adults not quarantined or undergoing treatment due to COVID-19 infection. Methods We searched 9 databases (2 Chinese-language) from December 31, 2019, to March 22, 2021. We included randomised controlled trials of interventions to address COVID-19 mental health challenges among people not hospitalised or quarantined due to COVID-19 infection. We synthesized results descriptively due to substantial h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The topic most studied (40.6%) was the treatment of COVID-19. 20 , 22 , 25 , 32 , 37 , 39 , 43 , 46 , 47 , 49 , 51 , 55 , 56 , 58 , 62–64 , 67–74 , 79 The population most studied (76.6%) was general COVID-19 patients, 18–23 , 26 , 27 , 29 , 31–34 , 36 , 37 , 39 , 42–44 , 46 , 47 , 49–65 , 67–76 , 79 but there were fewer (6.3%) studies concerning pregnant women 16 , 17 , 30 , 78 and children 28 , 30 , 77 , 78 with COVID-19, even no study concerning the elderly with COVID-19. ( Table 1 , Supplementary Material Table 1 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The topic most studied (40.6%) was the treatment of COVID-19. 20 , 22 , 25 , 32 , 37 , 39 , 43 , 46 , 47 , 49 , 51 , 55 , 56 , 58 , 62–64 , 67–74 , 79 The population most studied (76.6%) was general COVID-19 patients, 18–23 , 26 , 27 , 29 , 31–34 , 36 , 37 , 39 , 42–44 , 46 , 47 , 49–65 , 67–76 , 79 but there were fewer (6.3%) studies concerning pregnant women 16 , 17 , 30 , 78 and children 28 , 30 , 77 , 78 with COVID-19, even no study concerning the elderly with COVID-19. ( Table 1 , Supplementary Material Table 1 )…”
Section: Resultsmentioning
confidence: 99%
“…In the production phase of LSR, most of the LSRs registered 16–22 , 25 , 26 , 28–33 , 35 , 37 , 39–42 , 45–62 , 65–67 , 69–73 , 76–79 (81.2%) and wrote the protocol 16–35 , 37 , 39–43 , 45–67 , 69–73 , 76–79 (92.2%) before the study started. Less than one third of the LSRs searched the Chinese database 16–18 , 23 , 25 , 34 , 35 , 43 , 46 , 48 , 57 , 62–64 , 70 , 79 (25%), and less than half of the LSRs searched the preprint database 16 , 20 , 21 , 23–26 , 28 , 37 , 39 , 40 , 43 , 45 , 46 , 48 , 51 , 53 , 57 , 62–64 , 67 , 68 , 73 , 76 , 77 , 79 (42.2%), and two-thirds of the LSRs searched 12 COVID-19 databases 16 , 17 , 20–23 , 27 , 30 , 32 , 33 , 37–42 , 44–46 , 48 , 49 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially the case in COVID-19 research among trials with time pressures and insufficient research infrastructure, particularly in the earlier phases of the pandemic, which contributed to the conduct and publication of many poorly designed studies with sample sizes too small to answer the research questions being posed [ 72 ]. The set of trials included in the present review exceed what we have seen prior to COVID-19 or in other areas of COVID-19 mental health (e.g., [ 13 ]) in terms of failing to provide minimally transparent reporting, verification of origin, overall study quality, and the unusually large effects reported. For comparison, over 50% of trials reported SMD effect sizes of 2.0 or greater versus only 1 of 11 (9%) trials in the most recent pre-COVID-19 systematic review of ICU-based interventions [ 7 ].…”
Section: Discussionmentioning
confidence: 98%
“…The objective of the present sub-study is to synthesize evidence from RCTs on the effects of mental health interventions for people hospitalized with COVID-19 infection. Results from trials of interventions for people not quarantined or undergoing treatment due to COVID-19 infection have been reported elsewhere [ 13 ].…”
Section: Introductionmentioning
confidence: 99%